Aprendizaje basado en problemas para mejorar el rendimiento académico en matemáticas en los estudiantes de octavo año en la unidad educativa “Renán Olmedo González” - Vélez Sánchez, Adriana Carolina (2025)
This research evaluates the impact of Problem-Based Learning (PBL) on the mathematics performance of eighth-grade students at the Renán Olmedo González Educational Unit. A quasi-experimental design was used with two intact groups: group A (n=21) received traditional teaching, while group B (n=22) was taught using PBL. Both groups took a diagnostic test and a final test with eight items on whole numbers and fractions. To contextualise the experience, surveys were administered to students and teachers, and interviews were conducted with the institutional authority.